"THE INFLUENCE OF E-COMMERCE ON CONSUMER PURCHASING BEHAVIOUR: AN EXAMINATION OF YOUTH ONLINE SHOPPING TREND" - Dr. Rituraj Pant; Surbhi Chugh (International Educational Journal of Science and Engineering, 2025)
Along with technological advancements, consumer behaviour has also changed in terms of lifestyle, attitudes, preferences, and purchasing patterns. People can now access markets all over the world with great convenience thanks to the widely recognized digitalization trend. India, the seventh-largest nation in the world, has a large e-commerce population, especially among young people who choose to shop online because of time and financial constraints. They can access anything at any time with just one click. Customers now find it incredibly convenient to shop for anything they want thanks to e-commerce platforms. This study looks at Uttarakhand's youths' online shopping habits and how digital platforms affect their decisions to buy. Businesses can better adapt their internet marketing strategies to meet the preferences of younger consumers by using the insights gained from this research.